Validation of the lines of cornmon bean (Phaseolus vulgaris, DOR 482), in the eastern zone of EI Salvador. - Ventura, Rolando (2016)
This study was conducted during 1995 in the eastern region of El Salvador, formed by the departmcnts of Usulutan, San Miguel, Morazan and La Union, all of them traditionally bean cultivation areas, in particular during the second cropping period (august-september). Thirty six plots of 1000 m2 each were established to evaluate at the farm level the line of the common bean DOR 482. The statistical design was that of paired plots where the check was the local variety and the new technology was the DOR 482. Plots were managed based on each farmer's different technology. Agronomical, culinary and yield characteristics were measured. During the croppingcycle ten field trips were perfomed with a total of 196 farmers. Growing habit and yield were the agronomiccharacteristics of DOR 482 preferred by most farmers. Regarding culinary aspects, 57% chosed DOR 482 as softer, 64% as bettertasting, and88% as the one producing the thickest soup. As for yielding characteristics the average yield for the local varieties was 681,31 kg/ha (10,5 qq/mz) and the averagefor DOR 482 was 1034 kr/ha (15,93 qq/mz), a 51,8% increase over the local varieties.